Analisis Pengaruh Islamicity Performance Index terhadap Profitabilitas Bank Umum Syariah di Indonesia Tahun 2014 – 2018 - Nadiya Zahra Rahmatullah; Fifi Afiyanti Tripuspitorini (Journal of Applied Islamic Economics and Finance, 2020)
Sharia banking performance needs to be measured with an approach that is by sharia objectives in addition to using conventional approaches. An kalternative kto kthis kapproach kis kto kuse kthe Islamicity Performance Index. This study was conducted to pobtain pempirical pevidence pabout pthe peffect pof pIslamicity pPerformance pIndex pcomponents pon pthe pprofitability pof pIslamic pcommercial pbanks pin pIndonesia pwhich pis pproxied pby pReturn pon pAssets p(ROA). This research was conducted using seven samples of Islamic banks in Indonesia using the 2014-2018 quarterly financial reports. The sample selection method uses purposive sampling. The kdata kused kin kthis kstudy kare ksecondary kdata kobtained kfrom keach kIslamic kbank's kwebsite. The method used in this research is panel data regression using the eviews 10 application program. The results of this research indicate that simultaneously the selected component of the Islamicity Performance Index has a significant effect on the profitability of Islamic Commercial Banks in Indonesia. Partially, the profit sharing ratio and zakat performing ratio have no significant effect on the profitability of Islamic Commercial Banks in Indonesia. Meanwhile, the bequitable bdistribution bratio bhas ba bsignificant bpositive beffect bon bthe bprofitability bof bIslamic bCommercial bBanks bin bIndonesia.